Leaf phosphorus fractionation in rice to understand internal phosphorus-use efficiency - Hayes, Patrick E; Adem, Getnet D; Pariasca-Tanaka, Juan; Wissuwa, Matthias (Annals of botany, 2022)
Phosphorus (P) availability is often limiting for rice (Oryza sativa) production. Improving internal P-use efficiency (PUE) is crucial to sustainable food production, particularly in low-input systems. A critical aspect of PUE in plants, and one that remains poorly understood, is the investment of leaf P in different chemical P fractions (nucleic acid-P, lipid-P, inorganic-P, metabolite-P and residual-P). The overarching objective of this study was to understand how these key P fractions influence PUE. Three high-PUE and two low-PUE rice genotypes were grown in hydroponics with contrasting P supplies. We measured PUE, total P, P fractions, photosynthesis and biomass. Low investment in lipid-P was strongly associated with increased photosynthetic PUE (PPUE), achieved by reducing total leaf P concentration while maintaining rapid photosynthetic rates. All low-P plants exhibited a low investment in inorganic-P and lipid-P, but not nucleic acid-P. In addition, whole-plant PUE was strongly associated with reduced total P concentration, increased biomass and increased preferential allocation of resources to the youngest mature leaves. Lipid remodelling has been shown in rice before, but we show for the first time that reduced lipid-P investment improves PUE in rice without reducing photosynthesis. This presents a novel pathway for increasing PUE by targeting varieties with reduced lipid-P investment. This will benefit rice production in low-P soils and in areas where fertilizer use is limited, improving global food security by reducing P fertilizer demands and food production costs.